Bangla speech isolation from noisy auditory environment using convolutional neural network - Zaman, K M Tahzeem; Hasan, Zahid; Hossain, Mohd. Ibrahim (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.